SPECIFIC CHARACTERISTICS OF ORAL SPEECH (Scientific journal of the Fergana State University, 2024)
This article talks about the specific features of oral speech, the fact that pauses (pauses) in the speaker's active speech, tone, emphasis, and various gestures are of great importance in conveying the thought to the listener. The article describes the features of oral speech in comparison with written speech. A number of (extralinguistic) factors outside the language also have their influence on the realization of oral speech. Under the influence of these factors, the speaker chooses language tools in the process of communication. The results of the research conducted by the German scientist Heinz Rupp in 1964 emphasized the difference between oral speech and written speech and the need to pay special attention to oral speech in classes. Also, in the article, the implementation of written and spoken speech is given with the help of examples, and in written speech, the mental experience and state of a person is reflected using punctuation marks, exclamation, question, etc., and in spoken speech, it is explained in detail by tempo, tone, pause, and emphasis. It is stated that the phonetic phenomena listed above play an important role in teaching oral speech, and if the communicator does not follow the phonetic rules, the cognizant may misunderstand him or not understand him at all.